2014
DOI: 10.1039/c3cc47332e
|View full text |Cite
|
Sign up to set email alerts
|

Highly dispersed iron oxides on mesoporous carbon for selective oxidation of benzyl alcohol with molecular oxygen

Abstract: Highly dispersed iron oxide supported catalysts, prepared using HNO3-treated CMK-3 mesoporous carbons as supports, exhibit relatively high catalytic activity in selective oxidation of benzyl alcohol with oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 30 publications
(3 reference statements)
0
28
0
Order By: Relevance
“…The catalytic performance of Fe 3 O 4 /C was tested in the selective oxidation of benzyl alcohol with air as the oxidant source (Figure ). Fe 3 O 4 /C exhibits 93.6 % conversion of benzyl alcohol after 8 h of reaction, which is comparable with that of supported ultrafine iron oxide particles (<2 nm) reported previously and much higher than that of supported 5–10 nm α‐Fe 2 O 3 . The selectivity to benzaldehyde is nearly 100 %.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The catalytic performance of Fe 3 O 4 /C was tested in the selective oxidation of benzyl alcohol with air as the oxidant source (Figure ). Fe 3 O 4 /C exhibits 93.6 % conversion of benzyl alcohol after 8 h of reaction, which is comparable with that of supported ultrafine iron oxide particles (<2 nm) reported previously and much higher than that of supported 5–10 nm α‐Fe 2 O 3 . The selectivity to benzaldehyde is nearly 100 %.…”
Section: Resultsmentioning
confidence: 95%
“…Few of them are catalytically active under mild reaction conditions . Very recently, we reported that ultrafine iron oxide species (<2 nm) supported on carbon be active in the selective oxidation of benzyl alcohol with air as the oxygen source . This catalyst could work at low reaction temperatures (40–80 °C) and ambient pressure (1 atm) .…”
Section: Introductionmentioning
confidence: 99%
“…145,146 Schüth and co-workers successfully synthesized γ- 147 Black carbon-silica composites were obtained via a hard template approach. The key point in the synthetic procedure is to impregnate the Fe precursor into the carbon-silica composites, instead of the prepared CMK-5.…”
Section: Mesoporous Carbonmentioning
confidence: 99%
“…Noble metal [3][4][5][6] and metal oxide [7][8][9][10] catalysts are two types of materials widely used for alcohol oxidation reactions, but show drawbacks when used in practical applications. Noble metals are expensive and need to be prepared at the nanoscale to achieve the desired catalytic performance.…”
Section: Introductionmentioning
confidence: 99%